Evolution of the future network architecture of core network - Jiyan WANG; Yun LI; Xun DONG; Lei SHEN; Jingjian YI (Dianxin kexue)
At present,the mobile data traffic is growing rapidly,Based on the evolution trend of mobile communication network to 5G and NFV/SDN technology,the evolution direction of core network future architecture was presented.The demand for the core network of the service development and technical evolution,the core network status and future evolution direction of core network architecture were introduced.The result has guiding significance for the future development of the core network and network construction.